2005
DOI: 10.1073/pnas.0508010102
|View full text |Cite
|
Sign up to set email alerts
|

Visibility, visual awareness, and visual masking of simple unattended targets are confined to areas in the occipital cortex beyond human V1/V2

Abstract: In visual masking, visible targets are rendered invisible by modifying the context in which they are presented, but not by modifying the targets themselves. Here, we localize the neuronal correlates of visual awareness in the human brain by using visual masking illusions. We compare monoptic visual masking activation, which we find within all retinotopic visual areas, with dichoptic masking activation, which we find only in those retinotopic areas downstream of V2. Because monoptic and dichoptic masking are eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
105
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(120 citation statements)
references
References 40 publications
13
105
2
Order By: Relevance
“…That and further work (Tse et al, 2005) indicated a late component to dichoptic masking that arises after binocular combination. Our results and arguments here do not challenge that conclusion, but Baker et al (2007b) proposed that the stimulus used in those studies probably involved processes that were different from the contrast phenomena here and elsewhere.…”
Section: The Excitatory and Suppressive Exponents (P And Q)mentioning
confidence: 86%
“…That and further work (Tse et al, 2005) indicated a late component to dichoptic masking that arises after binocular combination. Our results and arguments here do not challenge that conclusion, but Baker et al (2007b) proposed that the stimulus used in those studies probably involved processes that were different from the contrast phenomena here and elsewhere.…”
Section: The Excitatory and Suppressive Exponents (P And Q)mentioning
confidence: 86%
“…Attention enhances the neural representation of target stimuli (Desimone and Duncan, 1995); it is considered a critical precursor for awareness by some (Driver and Mattingley, 1998;Dehaene et al, 2006) and a potential confound by others (Tse et al, 2005). Although the specific relationship between attention and consciousness remains unclear (Rees, 2007), it is evident that enhanced representation is not sufficient to produce awareness (Leopold and Logothetis, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Other work performed by Macknik and his colleagues (Tse et al, 2005;Macknik and Martinez-Conde, 2004) used a very different type of stimulus in which the mask and test contained similar oriented contours, but were not superimposed in either space or time. In an imaging study on humans (Tse et al, 2005), and a single-cell study on monkey (Macknik and Martinez-Conde, 2004), Macknik drew the opposite conclusion from us: that dichoptic influences arise after binocular summation. Our scheme (Fig.…”
Section: Implications and Comparison With Other Studiesmentioning
confidence: 99%